Strategy Marketing Narasi TV - Sikumbang, Syafei (Marcommers : Jurnal Marketing Communication and Advertising, 2022)
This study aims to find out how Narasi.tv's marketing strategy is in producing messages that will be broadcast through social media youtube. Every stage that exists must be the result of the thoughts of professional officers who are members of a solid team. The stages of the production process that we want to study are the production of the Narasi.tv program which starts with Pre-Production, Production and Post-Production. The research method used is a case study with a qualitative approach, and the type of research is descriptive, the researchers used interviews. The results of the research that the researcher found that the production strategy started from planning with research by choosing interesting materials and the best crew. The trending material is to be made into a talk show program, while in production chooses the best resource persons, then in post-production the editor edits by making it interesting in the first minute and adding illustrations both audio and video to support the editing results.